DESIGN AND FABRICATION OF FLUIDIC PLATFORM WITH INTEGRATED DUAL CHANNEL ELECTRODE SENSOR USING 3D PRINTING METHOD FOR DETECTION OF ASCORBIC ACID AND DOPAMIN - Khoirunnisaa', Fatimah
Microfluidics are technological systems capable of processing or manipulating liquids and gases at scales down to hundreds of micrometers. Even though this technology is relatively new, it is still very possible to develop a microfluidic platform in terms of design and fabrication processes. The Flow-cell application is an extension of the microfluidic platform. Flow-cell fabrication using the 3D printing method provides convenience in the fabrication process and provides benefits for the ease of obtaining the materials used. One of the flow-cell applications in the application of biosensors is the application of a flow-cell that is integrated with the analyte detection sensor electrode. The role of the flow-cell provides the effect of sample stability in the platform used for signal readings on the sensor electrodes. The integrated sensor electrode is used to detect analytes in the human body. In this final project, optimization of the design and fabrication of fluid platforms is carried out using a 3D printing method with resin materials using digital light processing (DLP) fabrication techniques. Optimization was carried out to obtain an optimal design of flow-cell 2 Channel sensor electrodes to prevent leakage and can be used for testing the detection of analytes in the body. Based on the tests carried out, it was found that the platform can be used for the detection of ascorbic acid and dopamin using the CV and DPV methods with SPCE/Bare and SPCE/AuNS. Based on the LOD calculation, the results showed that the CV and DPV methods with SPCE/Bare could still detect ascorbic acid in the range of 132.165 ?M and 57.256 ?M for the first channel platform and 128.529 ?M and 57.165 ?M for the second channel platform, respectively. Whereas dopamin has a low detection rate when using SPCE/Bare in the platform so that the detection of dopamin analytes is better using SPCE/AuNS. This can be seen through the LOD value of the dopamin DPV method using SPCE/AuNS of 1.131 ?M for the 1st channel platform and 1.459 ?M for the 2nd channel platform. This value corresponds to the detection range of ascorbic acid and dopamin in the blood plasma.